Electroacupuncture of the trigeminal nerve causes N-methyl-D-aspartate receptors to mediate blood-brain barrier opening and induces neuronal excitatory changes - Gong, Peng; Zhang, Shanshan; Ren, Li; Zhang, Jiangsong; Zhao, Yibin; Mao, Xuqing; Gan, Lin; Wang, Hao; Ma, Congcong; Lin, Yubo; Ye, Qinyu; Qian, Kecheng; et al. (Frontiers in Cellular Neuroscience, 2022)
The blood-brain barrier (BBB) is an important structure for maintaining environmental stability in the central nervous system (CNS). Our previous study showed that specific parameters of EA at the head points Shuigou (GV26) and Baihui (GV20) can open the BBB; however, the mechanism by which stimulation of body surface acupuncture points on the head results in peripheral stimulation and affects the status of the central BBB and the neuronal excitatory changes has not been elucidated. We used laser spectroscopy ，the In Vivo Imaging System (IVIS), immunofluorescence and immunoblotting to verified the role of the trigeminal nerve in BBB opening during EA, and we applied the central N-methyl-D-aspartate (NMDA) receptors blocker MK-801 to verify the mediating role of NMDA receptors in EA-induced BBB opening. Next, electroencephalogram (EEG) and in vivo calcium imaging techniques were applied to verify the possible electrical patterns of BBB opening promoted by different intensities of EA stimulation. The results showed that the trigeminal nerve plays an important role in the alteration of BBB permeability promoted by EA stimulation of the head acupoints. Brain NMDA receptors play a mediating role in promoting BBB permeability during EA of the trigeminal nerve, which may affect the expression of the TJ protein occludin, and thus alter BBB permeability. The analysis of the electrical mechanism showed that there was no significant change in the rhythm of local field potentials (LFP) in different brain regions across frequency bands immediately after EA of the trigeminal nerve at different intensities. However, the local primary somatosensory (S1BF) area corresponding to the trigeminal nerve showed a transient reduction in the delta rhythm of LFP with no change in the high-frequency band, and the action potential (spike) with short interspike interval (ISI) varied with EA intensity. Meanwhile, EA of the trigeminal nerve resulted in rhythmic changes in calcium waves in the S1BF region, which were influenced by different EA intensities. This study provides a research perspective and a technical approach to further explore the mechanism of EA-induced BBB opening and its potential clinical applications.